Detection of Theileria sp. in Grazing Cattle at Tamangapa Landfill Makassar - Sarah, Ruhil Aziz; Zulfikri Mustakdir; Irwan Ismail; Muhammad Fadhlullah Mursalim; Zainal Abidin Kholilullah; Fedri Rell; Adryani Ris; Rasdiyanah; Muhammad Muflih Nur; Abdul Wahid Jamaluddin; et al. (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
This study aims to detect the occurrence or absence of Theileria sp. parasitic infection in cattle grazed at the Tamangapa Makassar landfill. This research was conducted in January 2022- February 2023. Many samples used in this study were 43 samples from the total cattle population in the study site of 781 cows. The sample used in this study was blood made by Giemsa staining. The data analysis used in this study is descriptive analysis. The results showed that from 43 samples there were 31 negative samples and 12 samples were positive for Theileria sp. in cattle grazed at the Tamangapa Makassar landfill. This can be seen from observations under a microscope, which is seen the formation of rods or sticks in erythrocyte cells. The positive samples were divided into several categories, based on the sex of the presentation of Theileria sp. cases in female cattle (32.43%) higher than in males (0%). Based on age, the ≥2 (39%) year old category is higher than the <2 years old category (20%). The conclusion of this study was that in cattle at the Tamangapa Makassar landfill, there was a parasitic infection with Theileria sp. and the incidence presentation was 27.91%. The suggestion for this study is that further research should be carried out in the future using diagnostic tests in determining species using PCR. In addition, researchers can then pay better attention to conditions that can be risk factors for this disease.